Profiling of naturally occurring folates in a diverse soybean germplasm by HPLC-MS/MS. (1st August 2022) - Agyenim-Boateng, Kwadwo Gyapong; Zhang, Shengrui; Islam, Md Shariful; Gu, Yongzhe; Li, Bin; Azam, Muhammad; Abdelghany, Ahmed M.; Qi, Jie; Ghosh, Suprio; Shaibu, Abdulwahab S.; Gebregziabher, Berhane Sibhatu; Feng, Yue; et al.
Highlights: Conjugase treatment was sufficient for soybean folate extraction. 10-fold variation was observed for soybean folates, from 64.51 − 691.24 μg/100 g. 5-CHO-H4 folate was the most dominant folate vitamer in soybean. Folates are affected by accession type, ecoregion, and seed morphological traits. Soybean is a key candidate for folate biofortification. Abstract: Soybean is a rich source of folates. We optimised the extraction and detection of folates from soybean seeds by HPLC-MS/MS and analysed the folate content and composition of 1074 accessions. Total folate content ranged from 64.51 to 691.24 μg/100 g fresh weight, with 10-fold variation, and 60 elite accessions with over 400 μg/100 g of total folate were identified. The most abundant component was 5-CHO-H4 folate, which accounted for an average of 60% of total folate content. Seed-coat colour, seed weight, ecoregion, and accession type significantly affected soybean folate content. Furthermore, 5-CH3 -H4 folate correlated positively with seed protein ( r = 0.24***) and negatively with oil ( r = -0.26***). The geographical distribution of folate according to accession origin revealed that accessions from Northeast China contain higher amounts of total folate and 5-CHO-H4 folate. This study provides comprehensive and novel insights into the folate profile of soybean, which will benefit soybean breeding for folate enhancement.